Feet of Lead; Ships of Lead - John Buglass (Papers from the Institute of Archaeology, 2021)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> A survey of the tower of St Oswald’s Church, Filey, North Yorkshire recorded nearly 1500 graffiti spanning over 400 years. Visitors to the roof not only left their ‘mark’ but a range of iconography which throws light on such topics as literacy, fashion, a possible plague outbreak, occupations and personal relationships. The study of this graffiti produced a wealth of information on not only the people of Filey buton the early tourism to the town. The commonest images were the outlines of shoes, hands and sailing ships. A seemingly odd combination of imagery but one that, when looked at in detail, throws significant light on to the life and times in the 18th and 19th centuries in a Yorkshire coastal town. This paper will examine in more detail some of the information that can be obtained from a large collection of post-medieval graffiti of shoe and ship outlines that can be related to a specific time and place. Although the tower of St Oswald's contained examples of a wide range of graffiti including hands, fish, peel notations, love hearts and even a possible 'plague doctor' the focus of thispaper is primarily on the shoe outlines and ship images as there would simply not be space to discuss all the examples in detail. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <w:LsdException Locked="false" Priority=&quot
Keywords: Filey; shoes; ships; post-Medieval; church